Commencing undergraduates' self-efficacy and ability in finding academic resources: Are they improving? - Oliver, Beverley (SLEID, 2008)
Many studies suggest that young people, including commencing undergraduates are increasingly ―Net-savvy‖ and sophisticated users of information and communication technologies, devices and techniques, including their ability to find information. This paper reports on the self-efficacy and ability of two diverse cohorts of students (one in 1999–2000 and the other in 2004–5) in finding websites and journals for academic purposes, using the same methods. The preliminary results suggest that more recent cohorts (that is, those closer to what has been more recently described as the Net Generation) have greater confidence in their ability to find websites and journals for academic study, and that their confidence is justified. Deeper investigation suggests, however, that these Net Gen undergraduates are more confident than they should be, and that academic and information literacy programmes for commencing students are still necessary to ensure that our more Net-savvy students are also ―search-savvy.‖ Because of the differences in the cohorts tested in this research, the findings are limited; nevertheless, this small study does highlight discrepancies in students' self-efficacy and indicators of ability. Having more robust tools to assess students' abilities to find information, particularly for use with commencing undergraduates, would be a useful addition to university curricula. This article has been peer-reviewed and accepted for publication in SLEID, an international journal of scholarship and research that supports emerging scholars and the development of evidence-based practice in education. © Copyright of articles is retained by authors. As an open access journal, articles are free to use, with proper attribution, in educational and other non-commercial settings.